PARENTS DETERMINATION FACTORS INFLUENCING INCOMPLETE BASIC IMMUNIZATION FOR INFANTS IN SORONG CITY, WEST PAPUA PROVINCE - mustamu, alva cherry; Markus, Serly A. (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
Background: The implementation of complete Indonesian basic immunization has decreased in the period of 2012 - 2015. West Papua is one of the provinces with the lowest immunization coverage, which is 57.1% and the city of Sorong is only 21.9%.Objective:   to investigate  the determinant factors of parents in complete basic immunization of infants months in Sorong City, West Papua ProvinceMethods : This study was cross-sectional in design. The subjects consisted of a purposive sampling of 134 parents of children aged 1-5 years old, have incomplete  basic immunization from immunization records and who visit 10 health center in Sorong City. Data were collected from parents using questionaires  and immunization records. Logistic regression were used for data analysis.Results: Simultaneously, mother’s age, education level, occupational  status, number of children, experience of having children, distance to the place of immunization, knowledge, family support, immunization officers and attitudes did not affect the incompleteness basic immunization (f count 1.768). Only the number of children (t = 0.017) and immunization staff support (t = 0.044) which affected the incomplete immunization. sequentially, number of children ( = 0.003), immunization support staff ( = 0.004), distance to immunization site ( = 0.035) and attitudes ( = 0.027) which most contribute to incomplete immunization.Conclusion: Number of children, immunization officers support, distance to immunization site and attitudes which contribute to incomplete immunization.